Clinical and laboratory characteristics of measles in children in St. Petersburg during a rise in incidence 2023–2024 - N. S. Tian; I. V. Babachenko; Yu. V. Nesterova; K. V. Zhdanov (Журнал инфектологии, 2025)
Objective: to present the clinical and laboratory characteristics of measles in hospitalized children during the period of rising incidence in 2023-2024 in St. Petersburg.Materials and methods. А retrospective study was conducted at the clinic of the Federal State Budgetary Institution DNACIB FMBA of Russia, which included 68 patients aged from 3 months to 17 years 10 months hospitalized from January 2023 to April 2024. The patients underwent clinical and biochemical analyzes blood with assessment of indicators in comparison with age norms. Statistical processing of the results was carried out using Microsoft Excel and Statistica 7 for Windows. Differences were considered statistically significant at p<0.05.Results. In the first four months of 2024, the number of hospitalized patients exceeded the figure for all of 2023 by 2.4 times. Boys were hospitalized more often than girls (1.2:1). The median (Me) age of the patients was 6 years 9 months (interquartile range (IQR) 2 years 11 months – 10 years 11 months). 85% of children had no history of vaccination against measles. In 54% of cases, the epidemiological history could not be clarified. 27% of children had contact with measles in the family, less often – in treatment and prophylactic (10%), educational (3%) institutions and on the front door (6%). The median duration of illness at the time of hospitalization was 5.5 days (IQR 5–6 days). One of the leading complaints was fever (Me 39.0°C (IQR 38.5° – 39.5°C). In 24% of cases, the disease proceeded without symptoms of conjunctivitis. In 97% of children, a typical course of measles was noted with staged rashes. Spots Belsky-Filatov-Koplik were not detected in 6 children (9%). Clinical blood tests revealed leukopenia (63% of cases), lymphopenia (47%) and thrombocytopenia (44%). The described changes in laboratory parameters over time persisted only in 16%, 2% and 2% of children. The differences in the levels of leukocytes, lymphocytes, platelets on admission and discharge were statistically significant (p<0.001). In blood serum, the median level of C-reactive protein (CRP) was 6 mg/l (IQR 2–14 mg/l). An increase in the values of alanine (ALT) and aspartate aminotransferases (AST) was noted in 34% and 50% of the examined patients. Co-infection with other viruses (parvovirus B-19 and respiratory viruses) was detected in 14 patients (21%).Conclusion. In 2024, there was a significant increase in measles incidence. Children over 6 years of age, unvaccinated, with family contact with measles prevailed. Most patients suffered a typical form of measles with the formation of Belsky-Filatov-Koplik spots and the staged nature of maculopapular rashes. Laboratory examination revealed leukopenia, lymphopenia and thrombocytopenia, increased levels of transaminases. In 21% of cases, a combined viral-viral infection was observed.